Sosialisasi “Isi Piringku” Pada Remaja Putri Sebagai Upaya Pencegahan Stunting - Hesti Atasasih (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
My plate is a guide to daily food consumption. Nutrition Education "my plate contents" is important for adolescents to adopt a healthy eating pattern. In adolescence there is a speed of growth and physical, mental, emotional and social development. Ummu Sulaim Islamic boarding school is an Islamic boarding school for young women and organizes meals on a buffet basis, this causes the portion of the meal to not be in accordance with the guidelines for balanced nutrition. The purpose of this activity is to socialize "My Plate Contents" to young women as an effort to prevent stunting. The activity will be held in January-July 2019 at Pondok Pesantren Ummu Sulaim, Pekanbaru. The implementation began with an oral socialization of my plate contents to the principal, teachers, canteen and female students, followed by the preparation of poster procurement. Community service is carried out with methods of outreach, counseling, supervision, evaluation and advocacy. The result of community service is the knowledge of students about my plate contents increases after counseling, it can be seen from the results of pre-test and post-test increased by 38 points, with the lowest value of 70 and the highest value of 100. Supervision results found that Islamic boarding school had previously served nutritious food, but the type and amount did not match my plate contents, and after the implementation of this activity the provision of female students' meals was adjusted to the nutritional needs of the students, and in its application most of the female students had implemented the contents of my plate.